Formation and Features of Transnational Consciousness - Timalsina, Ramji (Medha: A Multidisciplinary Journal, 2023)
This theoretical review article argues that transnational consciousness deals with the way the border-crossing communities think about their life in connection with their past and future. As they are not physically in the homeland and not emotionally in the hostland, they are the people hanging in somewhere between these two spaces. Such a living condition and the thought pattern shapes the way they believe who they are. Consequently, they live with ethnic consciousness related to the homeland, hybridity that mixes up the life pattern from both the homeland and hostland, memories of homeland and imaginations of the possible life in the hostland, and finally with the double consciousness that works as a coping device in an unfulfilling new life away from the society of origin. To reach to this conclusion, I have reviewed the major transnational theorists from 1970s to early 2020s. Vertovec (2009) and Dahinden (2010) have been the major theorists as they summed up almost all the concepts related to transnationalism developed by 2000s. The findings of the researchers and opinions of the commentators on the formation of transnational life, literature and consciousness from the 2010s and early 2020s have been incorporated to establish the basic parameters to look at the formation and features of transnational consciousness.